LIBRARY DESIGN CONCEPT AT TARUTUNG, DIPONEGORO STREET WITH THE BATAK TOBA ARCHITECTURE APPROACH - Rizal S Pasaribu; Bhakti Alamsya; Ramadhani Fitri (Sean Institute, 2022)
Indonesia is a country famous for its natural and cultural wealth. One of the famous ones from Indonesia is from the tourism sector. To develop and advance the potential of the tourism sector in Lake Toba, especially in Lumban Julu District, and also as an effort to preserve culture, a museum is needed which is a generator for the revival of the area. In designing this library using the Neo-Vernacular Architecture approach of the Toba Batak culture. This is because the Neo-Vernacular Architecture approach elevates local wisdom, but with a touch that is in accordance with the current context.